Flexible and lead-free piezoelectric nanogenerator as self-powered sensor based on electrospinning BZT-BCT/P(VDF-TrFE) nanofibers - Liu, Jie; Yang, Bin; Lu, Lijun; Wang, Xiaolin; Li, Xiuyan; Chen, Xiang; Liu, Jingquan (Sensors and actuators. A. Physical., 2020)
[Display omitted] •Nanofibers based on BZT-BCT and P(VDF-TrFE) were successfully prepared through electrospinning method.•The nanofiber generator with 40% contents BZT-BCT exhibits more excellent output performance with the Voc of 13.01 V.•The generator is sensitive to the micro force and the Voc performs good linearty within the loading force.•The generator can response to different modes of deformation, even the small movements of human motion. Recently, the flexible and environmental-friendly piezoelectric generators have drawn much attentions due to the power-supplying apply applications of powering implantable and wearable devices. In this work, an environmental-friendly and flexible piezoelectric nanogenerator is proposed based on electrospinning nanofiber which is composed of 0.5Ba(Zr0.2Ti0.8)O3-0.5(Ba0.7Ca0.3)TiO3 (BZT-BCT) and polyvinylidene fluoride–trifluoroethylene P(VDF-TrFE). The as-prepared nanofiber mats with different amounts of doping of BZT-BCT nanoparticles varied from 0 wt% to 50 wt% are characterized by XRD and SEM. Based on the testing results, the nanofiber generator with 40 % content of BZT-BCT exhibits the excellent output performance, which produces the output voltage as high as 13.01 V under cyclic tapping under 6 N and 10 Hz, which is mostly attributed from the doping of the BZT-BCT with high piezoelectric coefficient. The generator can be deployed as the self-powered sensor, which can measure the tensile and compressive deformation, the movement of different parts of body. Due to the advantages of flexibility and environmental kindness, this developed nanogenerator has great potential for wearable and implantable devices.